Does high alveolar fluid reabsorption prevent HAPE in individuals with exaggerated pulmonary hypertension in hypoxia? - Betz, Theresa Maria; Dehnert, Christoph; Bärtsch, Peter; Schommer, Kai; Mairbäurl, Heimo (High altitude medicine & biology, 2015)
Abstract Betz, Theresa, Christoph Dehnert, Peter Bärtsch, Kai Schommer, and Heimo Mairbäurl. Does high alveolar fluid reabsorption prevent HAPE in individuals with exaggerated pulmonary hypertensio...